EKSISTENSI TUJUAN PENDIDIKAN ISLAM DALAM MENJAWAB KRISIS MORAL GENERASI DIGITAL - Amanatul Utami, Niki; Kamilatul MAola, Hilda; Sabrina Azahra, Qori; Awaliyah, Suci; Putri, Amelia; Rodianto, Rodianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of Islamic educational objectives in addressing the moral crisis of the digital generation amid the rapid development of information technology. The study employs a library research method with a descriptive qualitative approach by reviewing various books, scientific journals, and academic references related to the objectives of Islamic education, the moral crisis, and the challenges of the digital era. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that the objectives of Islamic education remain relevant in addressing the moral crisis of the digital generation through the reinforcement of spiritual values, moral conduct, digital ethics, and social responsibility. The concepts of tarbiyah, ta’lim, and ta’dib, along with the orientation toward fostering the “insan kamil” (the perfect human being), serve as a crucial foundation for building the character of the younger generation so they can withstand the negative influences of globalization and digitalization without losing Islamic values. This study offers a conceptual contribution to strengthening the position of Islamic education as a strategic solution in shaping the character of the digital generation and serves as a reference for educators, parents, and policymakers in designing an education that is both integrative and adaptable to the evolving times. However, this study is limited to a literature review; therefore, the findings remain theoretical and do not yet reflect direct implementation in the field. Consequently, further research is recommended to conduct an empirical study on the application of Islamic educational objectives in shaping the character of the digital generation within school, family, and community settings.